Learning a second language via print: On the logical necessity of a fluent first language - Caldwell-Harris, Catherine L.; Hoffmeister, Robert J. (Frontiers in Communication, 2022)
How Deaf children should be taught to read has long been debated. Severely or profoundly Deaf children, who face challenges in acquiring language from its spoken forms, must learn to read a language they do not speak. We refer to this as learning a language via print. How children can learn language via print is not a topic regularly studied by educators, psychologists, or language acquisition theorists. Nonetheless, Deaf children can do this. We discuss how Deaf children can learn a written language via print by mapping print words and phrases to sign language sequences. Challenges exist due to the inherent difficulty of this task. Additionally, Established, time-tested curricula for using a signed language to teach the print forms of spoken languages do not exist. We describe general principles for approaching this task, how it differs from acquiring a spoken language naturalistically, and empirical evidence that Deaf children’s knowledge of a signed language facilitates and advances learning a printed language.